Ethical issues are not exclusive to AI systems - Gomes, Otávio Santos; Braga e Silva, Glaúcia; Souza, Érica Ferreira de (Anais do Workshop sobre Aspectos Sociais, Humanos e Econômicos de Software (WASHES), 2025)
The increasing integration of software into daily life underscores the urgency of addressing ethical issues in software development. While significant attention has been given to Artificial Intelligence (AI), ethical concerns are equally relevant to other types of software due to their widespread presence and societal impact. This position paper highlights the importance of considering the social, human, and ethical aspects of software systems already embedded in our daily lives. To achieve this, we examine ethics from a philosophical perspective and argue why software developers must adopt an ethical perspective throughout the development process. Additionally, we explore the mirage of software neutrality and discuss perspectives of the field.